2022
DOI: 10.1177/25158163221096866
|View full text |Cite
|
Sign up to set email alerts
|

Patient-identified burden and unmet needs in patients with cluster headache: An evidence-based qualitative literature review

Abstract: Objectives: To qualitatively identify evidence-based literature related to the daily burden and unmet treatment and psychosocial needs of patients with cluster headache (CH). Methods: A literature search was conducted through October 20, 2020 across MEDLINE, EMBASE, CINAHL, and PsychInfo databases exploring quality of life (QoL) and disease burden in adults with CH. The search was restricted to full-text reports in peer-reviewed journals. Methodologic quality was assessed using the Critical Skills Appraisal Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Interestingly, neuromodulation studies of medically refractory CH failed to improve the quality of life, although the attack frequencies reduced. In a recent review by Freeman et al (23), significantly reduced quality of life was identified in a qualitative analysis of 11 studies conducted in the UK, Sweden, France, Korea, Germany, Denmark, Italy, Spain and Brazil. A significant impact on quality of life was also reported in Asian patients with CH, as reported in Korea (24) and China (25).…”
Section: Quality Of Lifementioning
confidence: 99%
“…Interestingly, neuromodulation studies of medically refractory CH failed to improve the quality of life, although the attack frequencies reduced. In a recent review by Freeman et al (23), significantly reduced quality of life was identified in a qualitative analysis of 11 studies conducted in the UK, Sweden, France, Korea, Germany, Denmark, Italy, Spain and Brazil. A significant impact on quality of life was also reported in Asian patients with CH, as reported in Korea (24) and China (25).…”
Section: Quality Of Lifementioning
confidence: 99%